Yogi Berra and the art of public affairs teaching. (2nd January 2019) - Schultz, David
ABSTRACT: A 25 retrospective on Journal of Public Affairs Education ( JPAE) reveals clear evolution and differences in issues of interest to public affairs teachers. Historical contingency and circumstances impact what should be taught. But there are also constants – repeated and recurrent themes that transcend time, authors, and editors. As the longest serving editor-in-chief or co-editor for Journal of Public Affairs Education ( JPAE) for nearly eight years, I learned a lot by reading the article submissions, and among the constants are the three themes – change, crisis, and continued belief in a single best way to teach or do things. This article reflects on these three themes and what they mean for the teaching and practice of public administration and affairs.